Description of larval instars of Dryinus tarraconensis Marshall, 1868 and Gonatopus baeticus (Ceballos, 1927) (Hymenoptera: Chrysidoidea: Dryinidae), parasitoids of the genus Dictyophara Germar (Hemiptera: Auchenorrhyncha: Dictyopharidae) - Guglielmino, Adalgisa; Parise, Gianluca; Bückle, Christoph (Zootaxa, 2015)
The last immature stage and the mature larva of Dryinus tarraconensis Marshall, 1868 and Gonatopus baeticus (Ceballos, 1927) are described for the first time. Features of immature and mature larvae of both species are discussed in the context of their implications for characterizing the subfamilies Dryininae and Gonatopodinae.